Internal consistency of the Sport Motivation Scale-II Questionnaire in the Brazilian context: potentialities and limitations - Júlia Barreira; Alexandre Slowetzky Amaro; Kaio Borges; Leonardo Leme Luque; Paula Teixeira Fernandes (Universidade Estadual Paulista (UNESP), 2022)
Abstract Aim: The purpose of this paper was to analyze the internal consistency of the Sport Motivation Scale-II (SMS-II) questionnaire based on three studies with sports practitioners in the Brazilian college context. Methods: All the three studies i) were carried out with students enrolled in higher education and engaged in sports training by their institution (n1 = 304; n2 = 441; n3 = 310); ii) used SMS-II as an instrument for data collection; iii) used the online procedure for data collection. The Confirmatory Factor Analysis was performed and Cronbach's Alpha (α), McDonald's Omega (Ω), and the correlation between items were used to assess internal consistency. Results: As potentialities, five dimensions of the SMS-II presented high values of internal reliability (α and Ω > 0.60). As a limitation, the dimension of introjected regulation showed low reliability (α and Ω < 0.40) in the three studies conducted by our group. The exclusion of item 16 enabled an increase in alpha, but without achieving satisfactory reliability in Study 1 (α = 0.46) and Study 2 (α = 0.31). In Study 3, the exclusion of item 7 improved the internal reliability of the dimension (α = 0.43) also without reaching satisfactory values of internal consistency. It was not possible to identify a problematic item, given that each item had a different influence in the three studies. Conclusion: We found good values of validity and internal consistency for the Brazilian version of the SMS-II. However, we suggest attention to the introjected regulation dimension when using the instrument in the Brazilian college context.